1990
DOI: 10.1037/0735-7044.104.4.583
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory conditioning of Hermissenda crassicornis..

Abstract: Bite-strike responses of Hermissenda crassicornis, elicited by chemosensory stimulation of the lips, were found to be modified when food extracts were paired with rotation-produced stimulation of the statocysts. Animals that received repeated pairings of an extract of 1 food (conditioned stimulus, CS) with rotation exhibited suppressed bite-strike responses to that food for up to 48 hr after training. This suppression was usually specific to the trained food and was pairing-specific as well. Discriminative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 31 publications
6
26
1
Order By: Relevance
“…When directly confronted with an aversive stimulus during testing, an animal may choose an aggressive response (i.e., bite-strike) as the most appropriate. However, this hypothesis does not account for the discrepancy between the present finding and those of Farley et al (1990) given the similarities in testing procedures. Although a single factor does not appear to account for this discrepancy, several methodological differences between this work and that of Farley et aI.-most notably, the use of contextual versus discrete cues-may have contributed to the difference (see General Discussion).…”
Section: Facilitation Of the Preparatory Clinging Response By A Reinfcontrasting
confidence: 50%
See 2 more Smart Citations
“…When directly confronted with an aversive stimulus during testing, an animal may choose an aggressive response (i.e., bite-strike) as the most appropriate. However, this hypothesis does not account for the discrepancy between the present finding and those of Farley et al (1990) given the similarities in testing procedures. Although a single factor does not appear to account for this discrepancy, several methodological differences between this work and that of Farley et aI.-most notably, the use of contextual versus discrete cues-may have contributed to the difference (see General Discussion).…”
Section: Facilitation Of the Preparatory Clinging Response By A Reinfcontrasting
confidence: 50%
“…The potential for distinct food preferences is supported by investigations of the chemosensory abilities of a broad range of intertidal gas-tropods (Audesirk & Audesirk, 1985;Kohn, 1961). For instance, Farley et al (1990) found that Hermissenda displayed different baseline response patterns to chemosensory stimuli (shellfish), thus suggesting a between-stimuli difference in salience. Similar differences between conditioning stimuli have been documented inPleurobranchea using chemosensory aversion learning (Davis et aI., 1980).…”
Section: Bite-strike Latencies At the 24-h Retention Intervalmentioning
confidence: 67%
See 1 more Smart Citation
“…The lack of stimulus specificity during chemosensory conditioning with molluscs is not inevitable, since considerable specificity has been observed in several reports (Colwill, Absher, & Roberts, 1988;Farley et al, 1990;Susswein, Schwarz, & Feldman, 1986). However, a key question is whether stimulus specificity is necessarily indicative of associative learning.…”
Section: The Combined Effects Of Differential Habituation Sensitizatmentioning
confidence: 99%
“…It is especially impressive that responding was greater to the CS+ than to the CS -in each of the experiments reported here independently of the specific stimulus identities. Research with other invertebrates has not always found conditioning effects to be orthogonal to the particular stimulus assignments (Farley et al, 1990;Mpitsos & Cohan, 1986). Third, Experiment 3 further establishes that nonreinforced presentations of a previously reinforced stimulus is an effective extinction procedure (Carew et aI., 1981;Colwill et aI., 1988).…”
Section: Discussionmentioning
confidence: 99%